2022
DOI: 10.1186/s12964-022-00886-4
|View full text |Cite
|
Sign up to set email alerts
|

Notch ankyrin domain: evolutionary rise of a thermodynamic sensor

Abstract: Notch signalling pathway plays a key role in metazoan biology by contributing to resolution of binary decisions in the life cycle of cells during development. Outcomes such as proliferation/differentiation dichotomy are resolved by transcriptional remodelling that follows a switch from Notchon to Notchoff state, characterised by dissociation of Notch intracellular domain (NICD) from DNA-bound RBPJ. Here we provide evidence that transitioning to the Notchoff state is regulated by heat flux, a phenomenon that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Accordingly, cellular meltome studies identified SDH subunits among the cell heat resistant proteins [68]. Clustering of heat-releasing mitochondria in cells allows for heat-requiring processes to take place [69]. With a melting point close to 60°C, SDH subunits have therefore the intrinsic capacity to work stably in a hot mitochondrial background reaching 50°C; a temperature experimentally verified in a growing series of cell lines [70].…”
Section: Figure 1 the Succinate Dehydrogenase (A) And Some Of Its Inh...mentioning
confidence: 99%
“…Accordingly, cellular meltome studies identified SDH subunits among the cell heat resistant proteins [68]. Clustering of heat-releasing mitochondria in cells allows for heat-requiring processes to take place [69]. With a melting point close to 60°C, SDH subunits have therefore the intrinsic capacity to work stably in a hot mitochondrial background reaching 50°C; a temperature experimentally verified in a growing series of cell lines [70].…”
Section: Figure 1 the Succinate Dehydrogenase (A) And Some Of Its Inh...mentioning
confidence: 99%
“…In this manner, signals generated downstream to the Notch pathway align the enhanced anabolic activity to mitochondrial energetic output. This pro-anabolic burst is terminated by a mitochondrial heat flux which destabilises the Notch transcriptional complex switching off the signalling pathway in a temperature-dependent manner [122].…”
Section: Notch Signalling Pathwaymentioning
confidence: 99%
“…Accordingly, cellular meltome studies identified SDH subunits among the cell heat-resistant proteins [ 72 ]. The clustering of heat-releasing mitochondria in cells allows for heat-requiring processes to take place [ 73 ]. With a melting point close to 60 °C, SDH subunits have therefore the intrinsic capacity to work stably in a hot mitochondrial background reaching 50 °C; a temperature experimentally verified in a growing series of cell lines [ 74 ].…”
Section: The Succinate Crossroad: Enzymes and Metabolites Stakeholdersmentioning
confidence: 99%